Chondroid Tenosynovial Giant Cell Tumor: A Rare Case Involving the Infratemporal Fossa - Albakri, Abdullah (Oman Med J, 2021)
Tenosynovial giant cell tumor (TGCT) is a benign soft-tissue neoplasm that rarely occurs in the craniofacial region. We report a case of a 27-year-old male who presented to our unit in September 2017 with severe temporomandibular joint (TMJ) pain and progressive limitation opening his mouth. Based on clinical and imaging examinations, a well-defined soft tissue lesion was identified within the right infratemporal fossa, causing pressure on the TMJ and the surrounding structures. The lesion was surgically excised through trans-mandibular and endoscopic approaches. Histopathology diagnosis revealed a rare chondroid subset of TGCT. At 18 months follow-up, the patient showed resolution of the jaw pain, good functional and esthetic outcomes, and no evidence of recurrence.